Shifting the color line : race and the American welfare state - Lieberman, Robert C., 1964- (Harvard University Press, 1998)
Despite the substantial economic and political strides that African-Americans have made in this century, welfare remains an issue that sharply divides Americans by race. Shifting the Color Line explores the historical and political roots of enduring racial conflict in American welfare policy, beginning with the New Deal.